2017
DOI: 10.1093/rheumatology/kex019
|View full text |Cite
|
Sign up to set email alerts
|

Value of multidisciplinary reassessment in attribution of neuropsychiatric events to systemic lupus erythematosus: prospective data from the Leiden NPSLE cohort

Abstract: In clinical practice NP events presenting in SLE are too often attributed to an immune-mediated origin. Multidisciplinary reassessment avoids misclassification in NPSLE. Multidisciplinary reassessment is the reference standard in NP events presenting in SLE and cannot be replaced by available attribution models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 19 publications
0
52
0
2
Order By: Relevance
“…Attribution of neuropsychiatric manifestations to SLE often requires a comprehensive, multidisciplinary approach to rule out mimics (infections, malignancy and others), taking into account the presence of risk (‘ favouring ’ ) factors (type and timing of manifestation, presence of generalised, non-neurological disease activity, abnormal neuroimaging and cerebrospinal fluid analysis, positive antiphospholipid antibodies [aPL]),97 as well as confounding factors favouring alternative diagnoses 98. The use of validated attribution models may aid in the diagnostic process 99 100…”
Section: Resultsmentioning
confidence: 99%
“…Attribution of neuropsychiatric manifestations to SLE often requires a comprehensive, multidisciplinary approach to rule out mimics (infections, malignancy and others), taking into account the presence of risk (‘ favouring ’ ) factors (type and timing of manifestation, presence of generalised, non-neurological disease activity, abnormal neuroimaging and cerebrospinal fluid analysis, positive antiphospholipid antibodies [aPL]),97 as well as confounding factors favouring alternative diagnoses 98. The use of validated attribution models may aid in the diagnostic process 99 100…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the model adopted, 19-38% of the NP events were attributed to NPSLE. In an independent prospective validation study, model A demonstrated an excellent specificity of 98% and poor sensitivity of 33%, while model B demonstrated a satisfactory specificity of 86% and fair sensitivity of 64% [16]. The intermodel discrepancy revealed the impact of altering the stringency of the decision rules.…”
Section: Clinical Significancementioning
confidence: 97%
“…However, these models have been developed with the expert opinion being the diagnostic gold standard, with no objective corroborating evidence. Therefore, the attribution of CD to SLE remains mainly reliant on the clinician's assessment, index of suspicion and clinical reasoning, which can benefit from the introduction of a collaborative multidisciplinary approach including neuropsychological, radiological and laboratory evaluations [21,39].…”
Section: Attribution Of CD To Slementioning
confidence: 99%